The Role of AI in Driving Sustainable HRM: A Phenomenological Study on the Use of People Analytics for Corporate Carbon Footprint Reduction - Parinsi, Welimas Kristina; Musa, Anugrah Dewi Lestari; Musa, Kartika Septiary Pratiwi (Journal Management & Economics Review (JUMPER), 2025)
This phenomenological study examines the role of artificial intelligence (AI) in advancing sustainable human resource management (HRM) practices, with a focus on reducing corporate carbon footprints through people analytics in Jakarta, Indonesia. As a megacity facing severe environmental degradation, Jakarta presents a critical context for exploring how AI-driven tools intersect with socio-cultural, ethical, and infrastructural realities. Through semi-structured interviews and focus group discussions with HR professionals and employees across diverse industries, the study reveals that while AI enhances precision in measuring emissions and optimizing eco-conscious workflows, its adoption is fraught with challenges. Key findings highlight tensions between technological efficiency and socio-economic inequities, ethical concerns over surveillance and algorithmic bias, and a pervasive "training gap" limiting AI’s accessibility. Participants emphasized the importance of participatory AI design, where frontline workers co-develop tools aligned with local practices, and collaborative models bridging public-private sectors. The study argues that AI’s potential in sustainable HRM hinges on balancing innovation with equity, ensuring tools are democratized, ethically governed, and integrated with human-centric values. By contextualizing these insights within Jakarta’s urban dynamics and global sustainability frameworks, such as the UN Sustainable Development Goals (SDGs), the research contributes actionable strategies for policymakers and organizations aiming to harmonize technological advancement with environmental and social justice.